Analgesia for acute gingivostomatitis: a national survey of pediatric emergency physicians. Issue 1 (27th July 2016) - MacLellan, Joe; Ali, Samina; Curtis, Sarah; Baserman, Jason; Dixon, Andrew
Abstract: Objectives: Gingivostomatitis is a common, painful pediatric presentation, and yet, few studies are available to guide management. We aimed to describe pediatric emergency physicians' current practice patterns, with respect to analgesic use in children with acute gingivostomatitis, in order to inform future studies. Methods: A national survey was conducted at all 15 national academic pediatric centres. Electronic surveys were distributed to pediatric emergency physicians using a modified Dillman protocol; non-respondents received paper surveys via post. Data were collected regarding demographic characteristics, clinical behaviour, factors that may influence practice, and future directions. Results: Response rate was 74% (150/202). Most physicians (72%) preferred the combination of acetaminophen and ibuprofen to either agent alone (ibuprofen 19%, acetaminophen 7%). The preferred second-line analgesics were oral morphine (48%, 72/150) and compounded topical formulas (42%, 64/150). The most commonly cited compounded agent was Benadryl plus Maalox (23%, 35/150). Clinical experience with a medication had the greatest influence on practice pattern, with 52% (78/149) strongly agreeing. The most commonly cited barrier to adequate analgesia was difficulty in the administration of topical or oral medication to children. Conclusions: As with many other painful conditions, the combination of acetaminophen and ibuprofen was preferred, followed by either agent alone. Oral morphine and topical compounded agents were also frequently prescribed. Regardless of patient age, physicians preferred oral morphine as a second-line agent to treat pain from severe gingivostomatitis. Future research will focus on determining which analgesic and route (oral or topical) is the most effective and best-tolerated choice. RÉSUMÉ: Objectif: La gingivostomatite est une affection douloureuse et fréquente chez les enfants, mais il existe peu d'études sur la prise en charge. Les auteurs, par l'enquête, visaient à faire état des pratiques actuelles parmi les médecins d'urgence pédiatrique en ce qui concerne l'utilisation des analgésiques chez les enfants souffrant d'une gingivostomatite aiguë, dans le but de donner une orientation à des études futures. Méthode: Il s'agit d'une enquête nationale, menée dans les 15 centres pédiatriques d'enseignement au pays. Les questionnaires en version électronique ont été envoyés aux médecins d'urgence pédiatrique selon une version modifiée de la méthode de Dillman; les non-répondants ont reçu un autre questionnaire, cette fois, par la poste, en version imprimée. Il y a eu collecte de données sur des caractéristiques démographiques, des habitudes cliniques, des facteurs susceptibles d'influer sur la pratique et des orientations futures. Résultats: Le taux de réponse s'est élevé à 74% (150/202). La plupart des médecins préféraient l'association d'acétaminophène et d'ibuprofène (72%) à l'utilisation seule de l'un ou l'autre de ces médicaments (ibuprofène : 19%; acétaminophène : 7%). Les analgésiques de deuxième intention utilisés le plus souvent étaient la morphine par voie orale (48% : 72/150) et les composés topiques (42% : 64/150). Le mélange mentionné le plus souvent était constitué de Benadryl et de Maalox (23% : 35/150). Le facteur qui influait le plus sur la pratique était l'expérience clinique d'un médicament; en effet, 52% (78/149) des participants se sont dits « tout à fait d'accord » sur l'énoncé. Enfin, le plus grand obstacle à une analgésie suffisante était la difficulté d'administration des médicaments topiques ou oraux aux enfants. Conclusions: Comme dans bien d'autres affections douloureuses, l'association d'acétaminophène et d'ibuprofène était la formule préférée, suivie de l'utilisation seule de l'un ou l'autre de ces médicaments. Étaient souvent prescrits aussi la morphine par voie orale et les composés topiques. Indépendamment de l'âge, les médecins préféraient la morphine par voie orale comme médicament de deuxième intention pour traiter la douleur causée par une gingivostomatite importante. Enfin, les futurs travaux de recherche devraient porter sur l'analgésique le plus efficace et la meilleure voie d'administration (orale ou topique) ainsi que sur la formule la mieux tolérée.